A Case Study of Use of MKCL SuperCampus in Teaching of Basics of Electronics Engineering to Enhance Classroom Interactions - Bhamre, Preeti; Jagtap, Ajit (Journal of Engineering Education Transformations, 2021)
Learning in classes is significantly improved by using ICT tools. This paper presents a case study of teaching a first year engineering subject of Electronics and Telecommunication with rigorous use of ICT tool named MKCL SuperCampus. The tool is used to pose a few questions intermittently during a lecture on students’ mobile and provide a real time summary of student responses for carrying out meaningful interactions, thereby leading to enhanced learning.